Role of departmental support structures and self-efficacy on physics student persistence: An examination of students’ experience from 19 physics graduate programs - Diana Sachmpazidi; Ben Van Dusen; Charles Henderson (Physical Review Physics Education Research)
Science, technology, engineering, and mathematics (STEM) graduate and doctoral programs experience consistently high attrition rates. Moreover, persistent disparities exist in gender and racial representation. Students from historically excluded backgrounds have lower retention rates than white and Asian American students. To date, little work has been done to understand the student experience and how it contributes to attrition or persistence. There is also a lack of information regarding the causes of demographic disparities in graduate student attrition. Past studies in this context primarily focused on student academic preparation and mentoring relationships. Although student self-efficacy is found to be a contributing factor for undergraduate student retention, there is currently minimal research on the role of self-efficacy in STEM graduate student retention. This study uses a sociological approach, based on the notion that the surrounding environment influences student experiences and behavior, to understand student retention in physics graduate education. In particular, we examine the relationship between four departmental support structures (mentoring and research experience, professional development, social and academic integration, and financial support) and students’ intentions to persist. We also examine the mediating role of academic self-efficacy in this relationship. We use the construct of self-efficacy under the assumption that self-efficacy is a dynamic construct influenced by, in this case, the academic environment. We use a mixed-method convergent design approach. We collected 396 student responses from 19 physics graduate programs across the United States, 20 follow-up semistructured student interviews, and 9 department leaders’ interviews. This study presents a retention model for graduate education that shows the critical role of student socioacademic integration and self-efficacy on intention to persist. Students’ in-depth interview data corroborate this finding, indicating that a supportive social and academic environment (e.g., working with peers on coursework, socializing, and communicating with faculty members and mentors) helps them in completing the program degree. Moreover, we found that departmental leaders are unaware of the struggles students experience due to the departmental environment (burnout, lack of socioacademic integration, and discrimination) and attribute students’ decisions to leave the program to factors external to the program, such as desire for career change. Student interview data emphasized the importance of cultural change toward supporting student learning and growth, improving work-life balance, and developing and maintaining healthier student-faculty relationships. The results of our study motivate further research to help us better understand how changes in these areas can impact student retention.